2016
DOI: 10.5194/cp-12-439-2016
|View full text |Cite
|
Sign up to set email alerts
|

Fossil plant stomata indicate decreasing atmospheric CO<sub>2</sub> prior to the Eocene–Oligocene boundary

Abstract: A unique stratigraphic sequence of fossil leaves of Eotrigonobalanus furcinervis (extinct trees of the beech family, Fagaceae) from central Germany has been used to derive an atmospheric pCO 2 record with multiple data points spanning the late middle to late Eocene, two sampling levels which may be earliest Oligocene, and two samples from later in the Oligocene. Using the inverse relationship between the density of stomata and pCO 2 , we show that pCO 2 decreased continuously from the late middle to late Eocen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 101 publications
(151 reference statements)
4
59
1
Order By: Relevance
“…Long-term CO2 decline likely provided the required underlying preconditioning for the EOT (DeConto and Pollard, 2003) and cool summers due to the coincidence of an eccentricity minimum and low amplitude obliquity at ~34 Ma provided a tipping point for sustained major Antarctic glaciation (Coxall et al, 2005). We conclude from the Prydz Bay record that in East Antarctica an EOT-1 ice sheet formed during a time of declining pCO 2 (Pagani et al, 2011;Pearson et al, 2009;Steinthorsdottir et al, 2016). The onset of diamict deposition, the prograding clinoforms in seismic data, the declining values of the CIA, and enhanced erosion and glacial weathering rates (Scher et al, 2011;Tochilin et al, 2012) all suggest that high-latitude climate deterioration and ice growth in the hinterland of Prydz Bay intensified 0.5 Myr prior to Oi-1 with major ice growth coincident with Eocene-Oligocene precursor glaciaton (Figure 8).…”
Section: Antarctic Warm Events Ice Growth and The Global Carbon Cyclementioning
confidence: 77%
See 1 more Smart Citation
“…Long-term CO2 decline likely provided the required underlying preconditioning for the EOT (DeConto and Pollard, 2003) and cool summers due to the coincidence of an eccentricity minimum and low amplitude obliquity at ~34 Ma provided a tipping point for sustained major Antarctic glaciation (Coxall et al, 2005). We conclude from the Prydz Bay record that in East Antarctica an EOT-1 ice sheet formed during a time of declining pCO 2 (Pagani et al, 2011;Pearson et al, 2009;Steinthorsdottir et al, 2016). The onset of diamict deposition, the prograding clinoforms in seismic data, the declining values of the CIA, and enhanced erosion and glacial weathering rates (Scher et al, 2011;Tochilin et al, 2012) all suggest that high-latitude climate deterioration and ice growth in the hinterland of Prydz Bay intensified 0.5 Myr prior to Oi-1 with major ice growth coincident with Eocene-Oligocene precursor glaciaton (Figure 8).…”
Section: Antarctic Warm Events Ice Growth and The Global Carbon Cyclementioning
confidence: 77%
“…Superimposed transient Eocene warming events are generally attributed to releases of atmospheric greenhouse gases from tectonic, metamorphic, ocean ventilation, methane hydrate (Dickens, 2003), or permafrost (DeConto et al, 2012 sources. Marine and terrestrial proxies show declining concentrations of atmospheric pCO 2 through the mid-to-late Eocene (Beerling and Royer, 2011;Pearson et al, 2009;Pagani et al, 2011;Anagnostou et al, 2016;Steinthorsdottir et al, 2016), but short-term fluctuations are not yet well represented due to the low temporal resolution of the records.…”
Section: Antarctic Warm Events Ice Growth and The Global Carbon Cyclementioning
confidence: 99%
“…Stomatal proxy pCO 2 reconstructions currently offer the highest-resolution record of Eocene pCO 2 , with almost 50 data points, compared to ∼10 each derived from marine alkenone and boron isotopes, and ∼20 from paleosols. The numerous studies, using various fossil angiosperms as well as the fossil gymnosperms Ginkgo and Metasequoia, in the three stomatal proxy methods currently in use mostly agree that the Eocene pCO 2 was more moderately elevated compared to what marine proxies and climate modeling suggest (McElwain, 1998;Kürschner et al, 2001;Royer et al, 2001;Greenwood et al, 2003b;Retallack, 2009;Smith et al, 2010;Doria et al, 2011;Grein et al, 2011;Roth-Nebelsick et al, 2012;Franks et al, 2014;Maxbauer et al, 2014;Liu et al, 2016;Steinthorsdottir et al, 2016;Wolfe et al, 2017). The discrepancy between the marine isotope and stomatal proxy pCO 2 results is considerable, with the marine isotopes recording pCO 2 currently assumed to be more consistent with the elevated Eocene temperatures recorded by numerous proxies and the workings of the Earth's climate system (Cramwinckel et al, 2018).…”
Section: Comparison To Existing Pco 2 Records and Implicationsmentioning
confidence: 99%
“…A recent global study of vegetation and terrestrial temperature change across the EOCT found a heterogeneous response in vegetation with cooling being well before the EOCT and being most prevalent in coastal areas (Pound and Salzmann). Another study using stomatal indices in fossil leaves recently found a decrease in CO2 levels, and implied cooling, beginning 1 to 2 million years before the EOCT (Steinthorsdottir et al, 2016). Thus, climate change preceding the EOCT is not unreasonable, and is a potential cause for the abundance changes reported here.…”
Section: Discussionmentioning
confidence: 52%